Hubungan antara Quality of Work Life dengan Kinerja Guru di Sekolah Menengah Pertama Negeri Kecamatan Pulogadung Kota Administrasi Jakarta Timur - Rifky Audrey Maulana; Neti Karnati; Winda Dewi Listyasari (Universitas Negeri Jakarta, 2017)
This study aims to determine whether there is a relationship between the quality of work life and teachers performance of Junior High School in Pulogadung District Area, East Jakarta. This research is a quantitative study with 2 variables in it, namely: (X) Quality of Work Life as independent variables and (Y) Performance as the dependent variable. Quality of work life is a set of real work situations in organizations which refers to the creation of performance improvement, employee involvement, as well as the satisfaction of the people involved in the organization in order to meet the expectations of the members of the organization. Performance is the attitude of the person which gift a contribution to reach the goal of work and the purpose of organization. The method used is survey method with the results of correlational studies. The population in this study is a Junior High School teacher in Pulogadung District Area, East Jakarta. Samples were taken by using a simple random sampling technique. The technique is based on the sample size used in this study were 65 teachers. Data collection for the variable Quality Of Work Life (X) and Performance (Y) using a questionnaire. Product Moment Correlation coefficients obtained, the coefficient r equal to 0.61079, and the results of testing the hypothesis with t test obtained t count equal to 6.123 is greater than t table of 1.669, then the alternative hypothesis (Ha) is expressed in a significant correlation coefficient received. The coefficient of determination of 0.3731 this means that the contribution of the quality of work life in schools to performance of Junior High School teacher in Pulogadung District Area, East Jakarta, amounting to 37.31%.